63.2k views
4 votes
If anyone can give an explanation with how to do this it would be nice, the modules on this homework application aren't cutting it for me.

If anyone can give an explanation with how to do this it would be nice, the modules-example-1

1 Answer

2 votes

Answer:

Explanation:

The given H(x) = √(2 - 2x^2) can be decomposed as follows: 2 - 2x^2 is g(x), the input to f(x), which in turn is f(x) = √x.

Thus, f(x) = √x is the first function. Here the input is simply x.

g(x) = 2 - 2x^2 is the second function. We use this function now as the input to f(x). These operations create the new function H(x) = (f°g)(x) = √(2 - 2x^2).

In summary:

f(x) = √x

g(x) = 2 - 2x^2

User JiratPasuksmit
by
4.9k points